External Factors Confronting Elderly Day Care in The Aftermath of The Covid-19 Crisis in Bangkok, Thailand - Na Pattalung, Nakarait; Chusri, Orranuch; Thongkong, Maniga (Journal of Food Health and Bioenvironmental Science, 2023)
The study aimed to investigate at the external factors affecting elderly day care centers after COVID-19 crisis in Bangkok, Thailand. The research method used was qualitative research, which included a review of the literature and in-depth interviews with three groups of stakeholders in Bangkok: two officers from the government sector, two elderly day care center owners and three caregivers from the private sector and three elderlies and two family members from the community sector. The semi-structured interview questions were open-ended and validated by two experts. The researcher then utilized the content analysis, case study research and PESTLE analysis techniques to examine the factor. Results showed the three perspectives (the government sector, the private sector, and the community sector). The factors that impact elderly care centers vary among different groups of individuals, with the government and private sectors having contrasting approaches. The government has implemented various measures to control the standards of elderly care centers and manage the spread of COVID-19. However, the private sector prioritizes business expansion and service provision, often neglecting government standards. This contrasts with the public sector, which values diverse factors such as standards for care centers, caregiver qualifications, disease control measures, service fees, convenience and the quality of services provided by the centers. In conclusion, elderly day care centers can better adapt to the challenges posed by the COVID-19 crisis and provide improved care for the elderly by enhancing affordability and integrating technology. Government should focus on improving certification standards and creating supportive living environments for the elderly.